Descending pronation patterns. Issue 4 (October 2016) - Wallden, Matt
Summary: This practical paper is a continuation of previous papers presented in this section discussing over-pronation. The focus of this article is the way that the body has evolved to handle pronation forces in a descending manner from trunk to foot. It was written to accompany the "Toe-tal Function" editorial in the 20:2 edition of JBMT, but didn't make it in for publication.